2008
DOI: 10.1111/j.1528-1167.2007.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐based morphometry of temporal lobe epilepsy: An introduction and review of the literature

Abstract: SUMMARYOriginally developed by Ashburner and Friston (2000) to detect differences in brain morphology between two or more groups of subjects, voxel-based morphometry (VBM) is a fully automated computerized quantitative magnetic resonance (MR) image analysis technique that does not rely on investigator expertise in neuroanatomy and is not restricted to the study of one brain region at a time, unlike manual region-of-interest volumetric analyses. As the method is automated and time efficient, analysis of brain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
328
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(374 citation statements)
references
References 102 publications
38
328
0
8
Order By: Relevance
“…This was as expected given that the inclusion criteria for patients involved a radiological diagnosis of HS. The surface‐based approach, to calculate per‐vertex cortical thickness, normalized FLAIR signal intensity and gray–white matter intensity contrast, demonstrated that while pediatric TLE patients did not show the widespread cortical thinning present in adult cohorts,16, 17, 18, 19 they nevertheless had morphological and intensity changes in ipsi‐lesional temporopolar neocortex. Furthermore, temporopolar FLAIR hyperintensities were more marked in patients with a history of febrile convulsions and blurring of the gray–white matter boundary was correlated with earlier onset of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was as expected given that the inclusion criteria for patients involved a radiological diagnosis of HS. The surface‐based approach, to calculate per‐vertex cortical thickness, normalized FLAIR signal intensity and gray–white matter intensity contrast, demonstrated that while pediatric TLE patients did not show the widespread cortical thinning present in adult cohorts,16, 17, 18, 19 they nevertheless had morphological and intensity changes in ipsi‐lesional temporopolar neocortex. Furthermore, temporopolar FLAIR hyperintensities were more marked in patients with a history of febrile convulsions and blurring of the gray–white matter boundary was correlated with earlier onset of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the hippocampus, there is a body of neuroimaging literature in adults, utilizing both volumetric and surface‐based methodologies, describing whole‐brain changes in gray matter volume,16 cortical thickness17, 18, 19 and T2/FLAIR intensity 20, 21. These changes are seen after several decades of illness duration, as seizures often start in childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, TLE imaging findings have confirmed the existence of temporal and extratemporal areas of neuronal loss (Keller & Roberts, 2008); with more recent studies demonstrating that microstructural abnormalities are extensive and pervasively distributed (Bonilha et al., 2015). Since most structural brain studies have investigated group‐wise differences, it remains unclear whether microstructural abnormalities in TLE are consistently observed across all patients (and could therefore be used to classify TLE vs. individuals without TLE), or whether there is a high degree of variability beyond a common underlying pattern.…”
Section: Introductionmentioning
confidence: 91%
“…It has been argued2 that non‐mnestic deficits in TLE might reflect extra‐temporal structural pathology,5, 6, 7 giving rise to the notion of TLE as a structural “network disease” 8. While structural “network disease” is unlikely to explain cognitive impairment in all cases,9 the underlying concept can be expanded to incorporate functional network disease as well.…”
Section: Introductionmentioning
confidence: 99%